Assessment of portion sizes and consumption of fruit and vegetables among Icelandic children in a school canteen with semi self-serving - Þóra Margrét Theodórsdóttir 1982- (2013)
This work was a part of a bigger study, Promeal, which is funded by Nordforsk. The Icelandic part of the study is being performed at the Icelandic Unit for Nutrition Research, University Hospital and University of Iceland and at the School of Education, University of Iceland. Researchers participating in this part of the study were: Anna Sigríður Ólafsdóttir which managed the project, Guðrún Kristín Sigurgeirsdóttir, Ingibjörg Kjartansdóttir, Ragnheiður Júníusdóttir and Þóra Margrét Theodórsdóttir. Background: Fruit and vegetable consumption among children is generally lower than recommended in most countries, and according to current knowledge the consumption in Iceland is among the lowest in amounts. Results from recent national surveys on Icelandic 6 year-old children’s and adult’s diet showed that the population consumes on average half the 500 g daily recommended amount of fruit and vegetables. However, according to Icelandic Health Directorate, children 10 years of age need smaller amounts, or 200 g of vegetables and 200 g of fruit per day. In the handbook for school canteens issued by the Health Directorate in 2010, suggested portions of vegetables served for lunch are 60 g of boiled vegetables and 50 g of raw vegetables. Furthermore, published standard images, as the Plate or the Food circle, and the 5 a Day poster are used for nutrition education in order to help consumers about food choices. The aim of the present study was to see a) how much the children generally serve themselves and how much of it they eat and b) if consumption and self-serving portions of fruit and vegetables are proportionally in balance with protein-rich foods and carbohydrate-rich foods on the plate, according to recommendations. Methods: The study was conducted in an elementary school in Reykjavík, in April 2013. Participants (n=19) were 10 year-old children; 9 girls and 10 boys. Data from 174 plates was collected during lunchtime, over five non-consecutive days. All food was weighed and pictures taken of the plates. Second ...